Photoperiod management in dairy herd (Indian Journal of Animal Production and Management, 2017)
Photoperiod management deals with manipulation of light and dark exposure to the animals during 24  hours duration. Shifting of cow from short day (8 hrs. of light) photoperiod (SDPP) to long day (16 - 18  hrs. of light) photoperiod (LDPP) improved performance of dairy animals. Light stimulates photoreceptor  cells of retina which subsequently relay inhibitory signal to pineal gland for melatonin secretion via retino  hypothalamic tract through a series of endogenous process. Melatonin secretes at night and duration of  secretion vary inversely with day length. Melatonin secretion from pineal gland further influences secretion  of number of other hormones like prolactin (PRL), gonadotropins and IGF-I. Alterations in these circulating  hormones influence growth, reproduction, lactation and immunity of dairy animals. Photo periodic response  was more with fluorescent, metal halide, high pressure sodium lighting. The recommended level of light  for the cow was 15 foot candle (162 lux) at 1m (3’) height from the stall floor. The 30 (close house) and  45 foot candle (open house) produce the good effect. The separation distance between two lights should  be 1.5 times more than mounting height (14 – 35 ft) depending on type of sheds. The optimum CRI of  light for calf house was 80. The recommended illumination level for milking parlour was 50 foot candles.  Duration of exposure to photoperiod directly affects growth of calves and heifers, as well as the mammary  tissue growth in heifers. Exposure to LDPP during the growth phase results larger and leaner animals at  maturity with greater mammary parenchymal growth and these effects are associated with greater yield in  first calver. Extending photoperiod (4 hrs.) using 160 lux light during winter season resulted in better growth  rate and early onset of puberty in buffalo heifers. Proliferation of mammary cells was better in SDPP dry  cows as compared to LDPP. Cows reared on LDPP during early lactation produced more milk (8 to 10%)  than on natural photoperiod. The effect of LDPP developed gradually and significantly after 3 - 4 weeks of  exposure. However, there is no carryover effect of photoperiod on milk production. LDPP produced more  milk yield may be due to elevated level of prolactin, growth hormone and IGF-I. Dry cow on SDPP for entire  dry period produces more milk (up to 3 kg) along with protein and fat in next lactation. SDPP also increased  feed intake (more than 1 kg) and improved the immunity in advanced pregnant dry cows. Duration of day  length during autumn and winter is generally shorter, but cattle and buffaloes when exposed to LDPP  show significant improvement of reproduction. Improved reproduction in cows reared under LDPP may be  associated with increased circulating Ca, P, vitamin D and A, total protein, hemoglobin, erythrocytes and  γ-globulins. Heifers reared under SDPP had increased lymphocyte proliferation and enhanced neutrophil  function than those reared under LDPP. SDPP exposure to dry cows improves immune status, uterine and  udder health immediately during post partum period. Somatic cell counts also reduced in cows exposed  to SDPP during dry period in contrast to cows under LDPP. Thus, proper manipulation of photoperiod improved lactating animal performance especially in terms of  milk, reproduction and health of animals.
Keywords: Dairy; Light; Management; Photoperiod